The Influence Of Service Quality Toward Customers’ Loyalty With Customers’ Satisfaction As Intervening Variable At PT. Arindo Jaya Mandiri - Anifa Fatma Zahriana; Achmad - Zaenuddin; M - Nahar (Admisi dan Bisnis, 2020)
This research is aimed to find out: (1) The influence of service quality toward customers’ loyalty at PT. Arindo Jaya Mandiri, (2) The influence of service quality toward customers’ satisfaction at PT. Arindo Jaya Mandiri, (3) The influence of customers’ satisfaction toward customers’ loyalty at PT. Arindo Jaya Mandiri, (4) The influence of service quality toward customers’ loyalty with customers’ satisfaction as intervening variable at PT. Arindo Jaya Mandiri. This research used a quantitative approach. The population of this research was the customers’ of PT. Arindo Jaya Mandiri with  purposive sampling the amount of 49 respondents. The result of this research was showed that: (1) service quality has positive significant influence toward customers’ loyalty which proven by the value of significance level 0,025<0,05; (2) service quality has positive significant influence toward customers’ satisfaction which proven by the value of significance level 0,000<0,05; (3) customers’ satisfaction has positive significant toward customers’ loyalty which proven by the value of significance level 0,004<0,05; (4) service quality has positive insignificant influence toward customers’ loyalty with customers’ satisfaction as intervening variable which proven by intervening coefficients value of 0,206  was less than direct influence coefficients value of 0,264